Hubungan Terpaan Iklan dan Citra Merek Bukalapak dengan Keputusan Pembelian Produk di Bukalapak - Nadira Octova Yogiyanti; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Technology is developing very rapidly, especially in the field of information and telecommunications. With this, many e-commerce startups have emerged in Indonesia. E-commerce is a means of buying and selling online that can facilitate consumers in the process of buying and selling online. Indonesia is the largest and fastest growing e-commerce market in Southeast Asia. This study uses the Strong Theory of Advertising Theory and Reasoned Action. This research is quantitative research with explanatory types. The sample in this study were men, women, attending 17-35 years, domiciled in the city of Semarang, with the provision of opening the Bukalapak advertisement, and having visited the Bukalapak online buying and selling site. The number of respondents is 80 people taken based on the purposive technique aside. Data analysis used was Chi-Square analysis with the help of SPSS. The results of the first hypothesis test, exposure to Bukalapak advertisements has a positive relationship with product purchasing decisions at Bukalapak with a value of 0.001 < 3,841. Then the Bukalapak brand image with product purchase decisions at Bukalapak has a positive relationship with a value of 0.008 < 3,841.